2021
DOI: 10.1038/s41598-021-86378-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 16S rRNA primer sets for characterisation of microbiota in paediatric patients with autism spectrum disorder

Abstract: intestinal microbiota is becoming a significant marker that reflects differences between health and disease status also in terms of gut-brain axis communication. Studies show that children with autism spectrum disorder (ASD) often have a mix of gut microbes that is distinct from the neurotypical children. Various assays are being used for microbiota investigation and were considered to be universal. However, newer studies showed that protocol for preparing DNA sequencing libraries is a key factor influencing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 63 publications
3
26
0
Order By: Relevance
“…In total, we analyzed 597 ASD-control pairs. To reduce the batch effects and noise associated with primer choice in the 16S datasets, a major confounder in microbiome analyses, we restricted the 16S datasets to include only those targeting the variable region V4 of the bacterial ribosomal RNA, a region exhibiting higher heterogeneity and lower evolution rates than other variable regions[97, 98, 99]. Our analysis included 16S datasets obtained targeting the V4 region exclusively, the V3-V4 region, or the V4-V5 region.…”
Section: Methodsmentioning
confidence: 99%
“…In total, we analyzed 597 ASD-control pairs. To reduce the batch effects and noise associated with primer choice in the 16S datasets, a major confounder in microbiome analyses, we restricted the 16S datasets to include only those targeting the variable region V4 of the bacterial ribosomal RNA, a region exhibiting higher heterogeneity and lower evolution rates than other variable regions[97, 98, 99]. Our analysis included 16S datasets obtained targeting the V4 region exclusively, the V3-V4 region, or the V4-V5 region.…”
Section: Methodsmentioning
confidence: 99%
“…This approach reduces diversity and simplifies the computational analyses, but it is not free from criticism [ 149 ]. For example, either the choice of the regions or the choice of the primers is known to affect the outcome deeply, introducing biases in the taxonomic picture, with artifactual under- or over-representation of some taxa [ 150 , 151 ]. Remarkably, it has also been demonstrated that few base pair mismatches can result in poor amplification of taxa otherwise abundant on the skin, such as Propionibacterium , especially when considering the V4 region [ 20 ].…”
Section: Methodological Considerations On Ngs Techniquesmentioning
confidence: 99%
“…As discussed, there are nine hypervariable regions in the 16S rRNA gene, and available primer sets typically amplify only a subset of these regions. Thus, the performance characteristics of the primer set chosen will influence the number of the analyzable reads ( 60 ) as well as the results of the analysis ( 61 ). For example, one study reports that the V4 primer set yields significantly more Bacteroides and lower Firmicutes reads than other primer sets tested; this is particularly notable given that the Bacteroidetes/Firmicutes ratio is a commonly reported metric ( 60 ).…”
Section: Fundamental Considerations In the Use Of Ngsmentioning
confidence: 99%